How to Engage in Practices of Critique? From a Universal Conception of the Good Life to the Contestation of Universals - Annemarije Hagen (Krisis, 2019)
Critical social theories examine social arrangements from the point of view of the obstacles that these structures pose to human flourishing, with the purpose of bringing about social change for the better. In this article, I contest the idea that these changes have to be guided by an idea of the good society. I argue that actual struggles are not guided by abstract ethical representations of the good life, but more negatively, by contestation of the limits of articulated universals by the ones who are excluded and marginalised.